The choroid plexus may be an underestimated site of tumor invasion to the brain: an in vitro study using neuroblastoma cell lines. Issue 1 (December 2015) - Vandenhaute, Elodie; Stump-Guthier, Carolin; Losada, María; Tenenbaum, Tobias; Rudolph, Henriette; Ishikawa, Hiroshi; Schwerk, Christian; Schroten, Horst; Dürken, Matthias; März, Martin; Karremann, Michael
Abstract Background The central nervous system (CNS) is protected by several barriers, including the blood–brain (BBB) and blood-cerebrospinal fluid (BCSFB) barriers. Understanding how cancer cells circumvent these protective barriers to invade the CNS is of crucial interest, since brain metastasis during cancer is often a fatal event in both children and adults. However, whereas much effort has been invested in elucidating the process of tumor cell transmigration across the BBB, the role of the BCSFB might still be underestimated considering the significant number of meningeal cancer involvement. Our work aimed to investigate the transmigration of neuroblastoma cells across the BCSFB in vitro. Methods We used an inverted model of the human BCSFB presenting proper restrictive features including adequate expression of tight-junction proteins, low permeability to integrity markers, and high trans-epithelial electrical resistance. Two different human neuroblastoma cell lines (SH-SY5Y and IMR-32) were used to study the transmigration process by fluorescent microscopy analysis. Results The results show that neuroblastoma cells are able to actively cross the tight human in vitro BCSFB model within 24 h. The presence and transmigration of neuroblastoma cancer cells did not affect the barrier integrity within the duration of the experiment. Conclusions In conclusion, we presume that the choroid plexus might be an underestimated site of CNS invasion, since neuroblastoma cell lines are able to actively cross a choroid plexus epithelial cell layer. Further studies are warranted to elucidate the molecular mechanisms of tumor cell transmigration in vitro and in vivo.